2013
DOI: 10.1097/aog.0b013e3182a5fdfd
|View full text |Cite
|
Sign up to set email alerts
|

Prophylaxis and Treatment of Anthrax in Pregnant Women

Abstract: Objective To review the safety and pharmacokinetics of antibiotics recommended for anthrax post-exposure prophylaxis and treatment in pregnant women. Data Sources Articles were identified in the PUBMED database from inception through December 2012 by searching the keywords ([“pregnancy]” and [generic antibiotic name]). Additionally, hand searches of references from REPROTOX, TERIS, review articles and Briggs’ Drugs in Pregnancy and Lactation were performed. Methods of Study Selection Articles included in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 113 publications
(154 reference statements)
0
33
0
Order By: Relevance
“…A recent systematic review reported no evidence of teratogenicity associated with doxycycline use during pregnancy; however, limited data and a lack of controlled studies were limitations (216). No reports of maternal hepatic toxicity associated with doxycycline use have been published (215)(216)(217). Rarely, fatty liver of pregnancy has occurred in patients who received high-dose intravenous tetracycline (215,218); however, the dosages administered in these cases exceeded what is recommended for the treatment of tickborne rickettsial disease.…”
Section: Pregnancy and Lactationmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent systematic review reported no evidence of teratogenicity associated with doxycycline use during pregnancy; however, limited data and a lack of controlled studies were limitations (216). No reports of maternal hepatic toxicity associated with doxycycline use have been published (215)(216)(217). Rarely, fatty liver of pregnancy has occurred in patients who received high-dose intravenous tetracycline (215,218); however, the dosages administered in these cases exceeded what is recommended for the treatment of tickborne rickettsial disease.…”
Section: Pregnancy and Lactationmentioning
confidence: 99%
“…Doxycycline has been used successfully to treat tickborne rickettsial diseases in several pregnant women without adverse effects to the mother; however, follow-up to address adverse effects to the fetus was limited (142,197). Chloramphenicol is a potential alternative treatment for RMSF during pregnancy; however, care must be used when administering the drug late during the third trimester of pregnancy because of the theoretical risk for gray baby syndrome (193,217).…”
Section: Pregnancy and Lactationmentioning
confidence: 99%
“…In preparation for the meeting, 2 systematic reviews were conducted; the first summarized the worldwide experience of 20 cases of anthrax in P/PP/L women ( 4 ), and the second evaluated the safety and pharmacokinetics of 14 antibiotics recommended for anthrax prophylaxis and treatment ( 5 ). Before the meeting, the CDC convened 5 workgroups: vaccines, antibiotic prophylaxis and treatment, other treatments and clinical considerations, health care planning, and communications.…”
Section: Methods For Guideline Developmentmentioning
confidence: 99%
“…In reproduction test in rats, 300 mg/kg of chloramphenicol for 4 weeks was found to potentially cause miscarriage and premature birth [21]. Chloramphenicol is recognized as Class C in the United States FDA pregnancy category [22]. In the present study, pregnant women with gestational ages ranging from 16 to 36 weeks were exposed to by 100 mg of transvaginal chloramphenicol per day for 7 days.…”
Section: Parameter Valuementioning
confidence: 96%
“…Second, this study did not determine the concentration of chloramphenicol in the umbilical cord blood. Maternal chloramphenicol readily crosses the placenta [22]. However, the maternal plasma concentration of chloramphenicol after trans-vaginal treatment was one one-thousandth that of the therapeutic concentration in oral and intravenous treatments.…”
Section: Parameter Valuementioning
confidence: 98%